Novel Therapeutic Approaches to Combat Antibiotic-Resistant Bacterial Strains Using Phage Therapy - Saxena, Money; Kumar, Manish; Panda, Swarup Kumar; Singhai, Manisha; Aswarthagari, Harinatha Reddy; Muthuswamy, Ragunathan (Journal of Neonatal Surgery, 2025)
The rise of antibiotic-resistant bacterial strains poses significant challenges to public health, necessitating innovative therapeutic strategies. This study investigates the efficacy of bacteriophage therapy as an alternative treatment against multidrug-resistant (MDR) strains of Escherichia coli, Pseudomonas aeruginosa, Acinetobacter baumannii, and Staphylococcus aureus. Isolated bacteriophages demonstrated high lytic activity, achieving a bacterial reduction of up to 99% at a multiplicity of infection (MOI) of 10. The biofilm disruption capability of phages was also assessed, revealing a reduction in biofilm mass by 70-85%. In vivo experiments in a murine model indicated that phage treatment improved survival rates to 80%, compared to 30% in the antibiotic-treated group and 0% in the untreated group. Moreover, a significant reduction in bacterial load was observed in the organs of phage-treated mice. These findings underscore the therapeutic potential of bacteriophage therapy in managing MDR bacterial infections and highlight its ability to disrupt biofilms effectively. The study concludes that bacteriophages present a promising alternative to traditional antibiotics, potentially addressing the urgent need for new therapeutic approaches in the face of rising antibiotic resistance.